Effect of BAU-Biofungicide, Neem Oil and a Nematicide on the Root-Knot (Meloidogyne javanica) of Papaya (Carica papaya) (Bangladesh Journal of Agricultural Research, 2012)
In a pot experiment, BAU-Biofungicide (Trichoderma harzianum) neem oil and  curaterr (carbofuran) 5G were tested against root-knot (Meloidogyne javanica)  of two papaya varieties Kashempuri and Deshi papaya. Seedlings were  inoculated with second stage larvae of M. javanica. Neem oil (5 ml/ 10g seeds)  and BAU-Biofungicide (1:4) were used as seed treatant and curaterr as side  dressing. Both the bio-agents significantly increased the root and shoot growth  of papaya plant and reduction of galls and eggmasses and suppressed the  development of J2, J3, and J4 and adult females of M. javanica. Efficacy of  BAU-Biofungicide was to reduce the gall and nematode development and to  increase plant growth was similar to nematicide curaterr. BAU-Biofungicide  gave higher effect in most of the growth characters compared to neem oil and  prevented the development of adult females and juveniles like nematicide  curaterr. DOI: http://dx.doi.org/10.3329/bjar.v37i2.11230 Bangladesh J. Agril. Res. 37(2): 271-277, June 2012